KEDISPLINAN SHOLAT SISWA DI SMK MUHAMMADIYAH 2 SLEMAN DITINJAU DARI PENGARUH PENGGUNAAN GADGET - Syahril Marzuki; Hanif Cahyo Adi Kistoro; Sutipyo Ru'iya (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2021)
In this age of globalization the development of the world of technology is very advanced and developing. Many students are very familiar with using gadgets, especially students. Students tend to use the gadget for many reasons, such as following trends, or to become more active on social media. With the intensity of students using gadgets, many students still do not have time limits in using it, so the obligation to worship, especially prayer, is often neglected and forgotten. This study aims to find out: the magnitude of the influence of the use of gadgets on the implementation of student prayer services This research is a survey research with a quantitative approach. The research subjects were 120 students. The technique of collecting data uses a questionnaire about the use of gadgets and the discipline of prayer services. Data analysis techniques with simple linear regression analysis using the help of the spss program. The results of this study indicate that there is a negative influence of the use of gadgets on the implementation of prayer services of 0.447%. It can be interpreted that the more often students use gadgets, the more negative impact on the prayer service of students.